SET kinetics of electrochemical metallization cells: influence of counter-electrodes in SiO2/Ag based systems. (1st March 2017) - Lübben, M; Menzel, S; Park, S G; Yang, M; Waser, R; Valov, I
Abstract: The counter-electrode material in resistively switching electrochemical metallization cells (ECMs) is a crucial factor influencing the nucleation of conductive filaments, the equilibrium electrode potentials, and kinetics in the devices, and hence the overall switching characteristics. Here, we demonstrate the influence of the counter-electrode (CE) material on the SET events and the importance of appropriate choice and combination of materials. The counter-electrode material influences the counter-electrode processes at the CE/insulator interface and consequently determines the metal ion concentration in the cells. We measured the switching kinetics for SiO2 /Ag based ECM cells using different counter-electrode materials with different electrocatalytic activities towards water reduction, namely platinum, ruthenium, and iridium oxide, as well as titanium nitride and tantalum. The experimental results are fitted using a physical simulation model and are analysed for the limiting factors for fast SET kinetics.